Study on chemical constituents, antioxidant and cytotoxic activities of Dracaena umbratica Ridl. AND Luvunga scandens Buch-Ham. / Raudhatul Jannah Mohd Zuki - Mohd Zuki, Raudhatul Jannah (2015)
Medicinal plants from two different families had been chosen for the phytochemical investigation. Attempt on isolation of dichloromethane extract of the leaves of Dracaena umbratica was not so successful due to the presence of only traces of compounds that overlapping heavily with chlorophyll. However, four pure compounds had been successfully isolated from the methanol extract of the leaves and dichloromethane extract of the roots of D. umbratica. Compound 3-0-[a-Lrhamnopyranosyl (l->4)-a-Z,-rhamnopyranosyl (l->4) -/?-D-glucopyranosyl]-25(^)- spirost-5-en-3/?, 17a-diol (Dl), spiroconazole A (D2) and mixture of stigmasterol-3-0 -/?-D-glucopyranoside and /?-sitosterol-3-0-/?-Z)-glucopyranoside (D3a) had been isolated using several techniques of chromatography from the methanolic extract of the leaves. All these compounds were saponins. A mixture of stigmasterol-3-0-/?-Z)- glucopyranoside and /?-sitosterol-3-0 -/?-Z)-glucopyranoside (D3b) had also been found in dichloromethane extract of the roots of this plant. Compound D3a and D3b were basically the same compound containing the mixture of two components, stigmasterol-3-<9-/?-Z)-glucopyranoside and /?-sitosterol-3-0-/?-D-glucopyranoside. However, the compositions of the two components were slightly different. The pure isolated compounds however exhibited good to moderate antioxidant activity (above 70% inhibition) when assayed by FTC and TBA assays. Cytotoxicity of all four pure compounds from D. umbratica against human breast cancer cell line (MCF-7) showed that compound Dl, D2, D3a and D3b exhibited very strong cytotoxicity with IC50 values lower than 10.0 (ag/mL. Therefore, those four compounds were considered as potent cytotoxic compounds against MCF-7. In addition, four pure compounds had been isolated from the dichloromethane extract of the roots of Luvunga scandens. Two of them were xanthones whereas another two pure compounds were coumarin and triterpene. The two isolated xanthones were new compounds which were determined as 10-hydroxy-5-methoxy-2,2-dimethylpyrano[3,2-6]xanthen-6(2H)-one (LI) and 10-(2,6-dihydro-5-methoxy-2,2-dimethyl-6 oxopyrano[J,2-Z>]xanthen-10- yloxy)-5-methoxy-2,2 -dimethylpyrano [3,2-6]xanthen-6(2//)-one (L2). However, the coumarin was found to be ostruthin (L3) while the triterpene was limonin (L4). These two were known compounds that had been isolated earlier from other species of the genus Luvunga. Ostruthin and LI exhibited good radical scavenging activity when assayed by DPPH with IC50 values of 9.5 and 12.7 |ag/mL, respectively while the other two compounds L2 and limonin showed poor radical scavenging activitiy with IC50 values of 42.8 and 85.3 \ig/mL, respectively. Results from FTC and TBA assays showed all the four compounds isolated from L. scandens possessed moderate antioxidant activity with percentage of inhibition higher than 70%. Results from cytotoxic activity indicated that only ostruthin showed significant IC50 value (23.5 |ag/mL) which can be considered as a cytotoxic compound against human breast cancer cell line (MCF-7) while the other three isolated compounds were inactive. This research has succeeded in isolating five compounds from D. umbratica and four compounds from L. scandens which served as important contribution to the existing knowledge of the phytochemicals of the genus Dracaena and Luvunga. At the same time, several antioxidants and cytotoxic compounds against human breast cancer cell line (MCF-7) had been discovered from this research.